XModeScore: a novel method for accurate protonation/tautomer‐state determination using quantum‐mechanically driven macromolecular X‐ray crystallographic refinement. Issue 4 (1st April 2016) - Borbulevych, Oleg; Martin, Roger I.; Tickle, Ian J.; Westerhoff, Lance M.
Abstract : XModeScore determines the correct protomeric/tautomeric state or mode of active‐site residues along with any bound ligand(s) using quantum‐mechanics‐based X‐ray refinement followed by post‐refinement scoring based on a combination of energetic strain (or ligand strain) and rigorous difference electron‐density analysis. Abstract : Gaining an understanding of the protein–ligand complex structure along with the proper protonation and explicit solvent effects can be important in obtaining meaningful results in structure‐guided drug discovery and structure‐based drug discovery. Unfortunately, protonation and tautomerism are difficult to establish with conventional methods because of difficulties in the experimental detection of H atoms owing to the well known limitations of X‐ray crystallography. In the present work, it is demonstrated that semiempirical, quantum‐mechanics‐based macromolecular crystallographic refinement is sensitive to the choice of a protonation‐state/tautomer form of ligands and residues, and can therefore be used to explore potential states. A novel scoring method, called XModeScore, is described which enumerates the possible protomeric/tautomeric modes, refines each mode against X‐ray diffraction data with the semiempirical quantum‐mechanics (PM6) Hamiltonian and scores each mode using a combination of energetic strain (or ligand strain) and rigorous statistical analysis of the difference electron‐density distribution. It is shown that using XModeScore it is possible to consistently distinguish the correct bound protomeric/tautomeric modes based on routine X‐ray data, even at lower resolutions of around 3 Å. These X‐ray results are compared with the results obtained from much more expensive and laborious neutron diffraction studies for three different examples: tautomerism in the acetazolamide ligand of human carbonic anhydrase II (PDB entries3hs4 and4k0s ), tautomerism in the 8HX ligand of urate oxidase (PDB entries4n9s and4n9m ) and the protonation states of the catalytic aspartic acid found within the active site of an aspartic protease (PDB entry2jjj ). In each case, XModeScore applied to the X‐ray diffraction data is able to determine the correct protonation state as defined by the neutron diffraction data. The impact of QM‐based refinement versus conventional refinement on XModeScore is also discussed.